Integration of CSR and travelers’ ascription of responsibility toward electric ride-hailing continuous intention in Vietnam - Pham-Hong, Truong; Nguyen, Loi Duc (Journal of Business Management and Economic Development, 2025)
In response to growing environmental concerns and the increasing emphasis on sustainable tourism, this study investigates the influence of corporate social responsibility (CSR), including environmental CSR and customer-related CSR, and travelers’ ascription of responsibility (AOR) on their continuous intention to use electric ride-hailing services while traveling in an emerging economy, Vietnam. The study employed a quantitative method using a questionnaire survey and data were collected through non-probability sampling methods. The results demonstrated that all three factors positively influenced travelers' continuous intention, with AOR exhibiting the most vital role. On top of that, customer-related CSR has a slightly higher impact on travelers' continuous intention compared with environmental CSR. The study contributes to understanding sustainable behavior in the context of tourism mobility and offers insights for promoting green transportation models. The findings also highlight the need for combined efforts from both service providers and travelers, suggesting strategies that integrate individual awareness, customer-oriented CSR actions, and environmental commitment.